Menolong Klub, Mengecam Suporter, Menjaga Pasar : Bingkai Berita dan Kebijakan Redaksi Desk Olahraga Jawa Pos dalam Pemberitaan Kerusuhan Bonek 4 September 2006 - PRASTYA, NARAYANA MAHENDRA (Jurnal Komunikator, 2016)
News is construction from social reality. The same fact and/or issue can be published in different frame in different media. In news processing, media is influenced by internal and external factors.This research aims to know how the news frame about Persebaya Surabaya fans chaos September 4th, 2006, in Jawa Pos newspaper. This research use two kinds of data sources. First is the news and second is interview with sport desk in Jawa Pos newsroom. The interview is being held in order to confirm the result of news analysis.The news than analyse with frame method. The result is Jawa Pos frame is Persebaya Surabaya does not deserve to be punished in this case. The supporters must take responsibility in this chaos.The Jawa Pos newsroom said that they have interest to protect Persebaya from punishment. Because, if Persebaya is being punished, Jawa Pos lost the news resources that can attract many readers. Meanwhile, Jawa Pos show their critical view for supporters in order to educate the public. Keywords :Â frame analysis, newsroom management, sport communication, sport newsÂ